Virus Innexins induce alterations in insect cell and tissue function. (April 2017) - Hasegawa, Daniel K.; Erickson, Stephanie L.; Hersh, Bradley M.; Turnbull, Matthew W.
Graphical abstract: Highlights: Expression of polydnavirus innexins ( vinnexins ) and host inx2 alter cell morphology. Ectopic inx2 but not vinnexins alters dye transfer between cells. Inhibition of gap junctions inhibits cellular encapsulation. Global ectopic expression of inx2 and vnxG is lethal in transgenic Drosophila. Abstract: Polydnaviruses are dsDNA viruses that induce immune and developmental alterations in their caterpillar hosts. Characterization of polydnavirus gene families and family members is necessary to understand mechanisms of pathology and evolution of these viruses, and may aid to elucidate the role of host homologues if present. For example, the polydnavirus vinnexin gene family encodes homologues of insect gap junction genes (innexins) that are expressed in host immune cells (hemocytes). While the roles of Innexin proteins and gap junctions in insect immunity are largely unclear, we previously demonstrated that Vinnexins form functional gap junctions and alter the junctional characteristics of a host Innexin when co-expressed in paired Xenopus oocytes. Here, we test the effect of ectopic vinnexin expression on host cell physiology using both a lepidopteran cell culture model and a dipteran whole organism model. Vinnexin expression in the cell culture system resulted in gene-specific alterations in cell morphology and a slight, but non-statistically significant, reduction in gap junction activity as measured by dye transfer, while ectopic expression of a lepidopteran innexin2 gene led to morphological alterations and increase in gap junction activity. Global ectopic expression in the model dipteran, Drosophila melanogaster, of one vinnexin ( vinnexinG ) or D. melanogaster innexin2 (Dm- inx2 ) resulted in embryonic lethality, while expression of the other vinnexin genes had no effect. Furthermore, ectopic expression of vinnexinG, but not other vinnexin genes or Dm- inx2, in D. melanogaster larval gut resulted in developmental arrest in the pupal stage. These data indicate the vinnexins likely have gene-specific roles in host manipulation. They also support the use of Drosophila in further analysis of the role of Vinnexins and other polydnavirus genes in modifying host physiological processes. Finally, our findings suggest the vinnexin genes may be useful to perturb and characterize the physiological functions of insect Innexins.